2013
DOI: 10.1021/ja310897r
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electrodeposition of Crystalline Silicon at Low Temperatures

Abstract: An electrochemical liquid-liquid-solid (ec-LLS) process that yields crystalline silicon at low temperature (80 °C) without any physical or chemical templating agent has been demonstrated. Electroreduction of dissolved SiCl(4) in propylene carbonate using a liquid gallium [Ga(l)] pool as the working electrode consistently yielded crystalline Si. X-ray diffraction and electron diffraction data separately indicated that the as-deposited materials were crystalline with the expected patterns for a diamond cubic cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
78
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 32 publications
2
78
0
Order By: Relevance
“…[14] Applying a large negative potential should therefore assist in the formation of crystalline Si x Ge 1Àx , together with amorphous Si. Figure 6 shows the morphology of electrodeposited Si x Ge 1Àx .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Applying a large negative potential should therefore assist in the formation of crystalline Si x Ge 1Àx , together with amorphous Si. Figure 6 shows the morphology of electrodeposited Si x Ge 1Àx .…”
Section: Resultsmentioning
confidence: 99%
“…[13] The same technique was also used to deposit silicon at 80 8C in gallium. [14] Our group has extensively investigated the electrodeposition of Ge and of Si x Ge 1Àx from ionic liquids that led to the formation of amorphous thin films. [15][16][17][18] Germanium electrodeposition was studied by in situ STM and STS.…”
Section: Introductionmentioning
confidence: 99%
“…Abedin et al [12] reported the initial nanoscale electrodeposition of silicon on the room-temperature IL 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide saturated with SiCl 4 . Gu et al [13] indicated the presence of crystalline silicon at low temperature in an electrochemical liquid-liquid-solid process, wherein SiCl 4 was dissolved in an electrolyte system. Zhang et al [14] reported an efficient method to prepare crystalline Si from SiCl 4 at a low temperature of 100°C with IL [N4441]TFSI as the electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the rich variety of issues discussed in the ten papers published in this Special Issue, there is still a wealth of issues that deserve at least a brief comment in this Introduction. The study of liquid metals under microgravity conditions is throwing light on several key aspects of solidification [12,13]. The use of liquid-metal solutions to produce greener crystalline silicon is expected to provide a practical way to produce this old but still-essential material [14].…”
mentioning
confidence: 99%